# |
ODE |
Mathematica |
Maple |
\[
{}\left (x^{2}-4\right ) y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x y-3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {3 y}{1+x}-y^{2}
\] |
✓ |
✓ |
|
\[
{}\sin \left (y\right )+\left (x +y\right ) \cos \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (y\right )+\left (1+x \right ) \cos \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right )+2 y^{\prime } \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = 2 x^{2}+2 y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +2 y}{x +2 y+3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +2 y}{2 x -y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}+\tan \left (\frac {y}{x}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y^{2}+3 y^{2}+x +3
\] |
✓ |
✓ |
|
\[
{}1-\left (x +2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\ln \left (y\right )+\left (\frac {x}{y}+3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+1-y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-3 y = 12 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = y^{2}+x y+x^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x +2\right ) y^{\prime }-x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{3} y^{\prime } = y^{4}-x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 y-\frac {16 \,{\mathrm e}^{4 x}}{y^{2}}
\] |
✓ |
✓ |
|
\[
{}2 y-6 x +\left (1+x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{2}+\left (x^{2} y+10 y^{4}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime }-x y^{2} = 6 x \,{\mathrm e}^{4 x^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (y-x +3\right )^{2} \left (y^{\prime }-1\right ) = 1
\] |
✓ |
✓ |
|
\[
{}x +y \,{\mathrm e}^{x y}+x \,{\mathrm e}^{x y} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}-y^{2} \cos \left (x \right )+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{3}-y^{3} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{2} {\mathrm e}^{x y^{2}}-2 x +2 x y \,{\mathrm e}^{x y^{2}} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{4 x +3 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \tan \left (6 x +3 y+1\right )-2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{4 x +3 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \left (6 y+{\mathrm e}^{x^{2}}\right )
\] |
✓ |
✓ |
|
\[
{}x \left (1-2 y\right )+\left (y-x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+3 x y = 6 \,{\mathrm e}^{-x^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+3 y = {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y = t^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = \operatorname {Heaviside}\left (t -4\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \operatorname {Heaviside}\left (t -3\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \operatorname {Heaviside}\left (t -3\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left \{\begin {array}{cc} 0 & t <1 \\ 1 & 1<t <3 \\ 0 & 3<t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 \delta \left (t -2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \delta \left (t -2\right )-\delta \left (t -4\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 4 \delta \left (t -1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = \delta \left (t -2\right )
\] |
✓ |
✓ |
|
\[
{}y y^{\prime }+y^{4} = \sin \left (x \right )
\] |
✗ |
✓ |
|
\[
{}{y^{\prime }}^{2}+y = 0
\] |
✓ |
✓ |
|
\[
{}2 x -1-y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x -y-y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {x}{y}
\] |
✓ |
✓ |
|
\[
{}3 y \left (t^{2}+y\right )+t \left (t^{2}+6 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {2 y}{x}-3
\] |
✓ |
✓ |
|
\[
{}y \cos \left (t \right )+\left (2 y+\sin \left (t \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {y}{x}+\cos \left (y\right )+\left (\ln \left (x \right )-x \sin \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (x^{2}-1\right ) \left (x^{3}-3 x \right )^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x^{2}\right ) x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x}{\sqrt {x^{2}-16}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x \ln \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-2 x -10}{\left (x +2\right ) \left (x -4\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-x^{2}+x}{\left (1+x \right ) \left (x^{2}+1\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\sqrt {x^{2}-16}}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (-x^{2}+4\right )^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x^{2}-16}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (x \right ) \cot \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x \right )^{3} \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 x^{3}-x +2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (2 t \right )-\cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\cos \left (\frac {1}{x}\right )}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\ln \left (x \right )}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (x -4\right ) y^{3}}{x^{3} \left (y-2\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x y+y^{2}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}4 x \left (x^{2}+y^{2}\right )-5 y+4 y \left (x^{2}+y^{2}-5 x \right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = \sin \left (x \right )^{4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 x -3 y+\left (2 y-3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \cos \left (x y\right )+\sin \left (x \right )+x \cos \left (x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{-x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x^{2}-x +1}{\left (x -1\right ) \left (x^{2}+1\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}}{\sqrt {x^{2}-1}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x \right ) \cos \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {4 x -9}{3 \left (x -3\right )^{{2}/{3}}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+t^{2} = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+t^{2} = \frac {1}{y^{2}}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = y+\frac {1}{1-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{{1}/{5}}
\] |
✓ |
✓ |
|
\[
{}\frac {y^{\prime }}{t} = \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 t^{2}-t y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \sqrt {t}
\] |
✓ |
✓ |
|